Economic Competitiveness and Quality of Human Resources in West Sumatra - Febrina Harahap, Erni; Helmawati, Helmawati; Rahmi, Siti; Ramadhani, Zaqiah; Mora, Mora (KnE Social Sciences, 2022)
Economic development is essentially an effort to improve people’s welfare through increasing and promoting equitable distribution of people’s income. The logical consequence of regional development in the current era of globalization is an increasingly sharp level of direct competition in the marketing of goods and services, both in the domestic market and the international market, for all regions in the national territory. The purpose of this study was, first, to analyze the characteristics and level of competitiveness of the regional economy and human resources in districts and cities in West Sumatra. Secondly, we aimed to investigate the relationships between regional economic performance, human resources and typology between regions in West Sumatra. This research used descriptive qualitative and quantitative methods and analyses. To determine the pattern and structure of regional economic growth, the Klassen typology was used. Then to examine the overall ranking of regional economic competitiveness, the average and standard deviation of the main indicator were calculated. The results indicated that the highest economic performance and quality of human resources were in the city of Padang, followed by Bukittinggi, Padang Panjang, Payakumbuh, and Solok. The lowest competitiveness was dominated by regencies such as Solok Selayan, Pesisir Selatan, and the Mentawai Islands. This was also supported by the findings of Klassen’s typology. Keywords: competitiveness, region, Klassen typology, performance